About residual stresses after rolling and exfoliation of two-ply stripe - Valeriy V Struzhanov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2010)
The residual stress definition problem was solved for stripe after rolling in one mill. Lengthwise residual stresses are basic cause of the defect initiation of stripe geometry of the buckles or corrugation type. Lengthwise residual stresses exist in the stripe with transversal residual stresses. These stresses induce the exfoliation of multi-layer stripes. The qualitative model for the two-ply stripe exfoliation under pressure of extension transversal residual stresses field was obtained subject to equality of the stripe materials stress-strain properties. The cause of the stepwise (unexpected) exfoliation was defined. The layer may be depressed essentially wanting the destruction (exfoliation) binding stripe.